Letter from David C. Pierson - David C. Pierson:::::: (1970)
In this November 18, 1970 letter, Assemblyman-Elect David C. Pierson thanks Jane Tolmach and Adele Leopold for their reminder about the Key Women Award Party. He encloses a list of women volunteers who were instrumental in his successful campaign for the 65th Assembly District so they may be honored at the event.